Exome sequencing identifies ATP4A gene as responsible of an atypical familial type I gastric neuroendocrine tumour. (11th February 2015) - Calvete, Oriol; Reyes, Jose; Zuñiga, Sheila; Paumard-Hernández, Beatriz; Fernández, Victoria; Bujanda, Luís; Rodriguez-Pinilla, María S.; Palacios, Jose; Heine-Suñer, Damian; Banka, Siddharth; Newman, William G.; Cañamero, Marta; et al.
Abstract : Gastric neuroendocrine tumours (NETs) arise from enterochromaffin-like cells, which are located in oxyntic glands within the stomach. Type I tumours represent 70–80% of gastric NETs and are associated with hypergastrinaemia, chronic atrophic gastritis and achlorhydria. Gastrin is involved in the endocrine regulation of gastric acid production. Most type I gastric NETs are sporadic, have a good prognosis and their genetic basis are unknown. We performed an exome sequencing study in a family with consanguineous parents and 10 children, five of whom were affected by type I gastric NET. Atypical clinical traits included an earlier age of onset (around 30 years), aggressiveness (three had nodal infiltration requiring total gastrectomy and one an adenocarcinoma) and iron-deficiency rather than megaloblastic anaemia. We identified a homozygous missense mutation in the 14th exon of the ATP4A gene (c.2107C>T), which encodes the proton pump responsible for acid secretion by gastric parietal cells. The amino acid p.Arg703Cys is highly conserved across species and originates a change of one of the transmembrane domains that avoids the liberation of protons from cells to stomach. This is consistent with the achlorhydria that was observed in the affected individuals. No germline or somatic mutations in the ATP4A gene were found in sporadic gastric NET patients. Based on the results of this large family, it seems that this atypical form of gastric NET has an earlier age of onset, behaves more aggressively and has atypical clinical traits that differentiated from other studied cases.